Sugar- and Artificially-Sweetened Beverages and Cancer Mortality in a Large U.S. Prospective Cohort - McCullough, Marjorie L; Hodge, Rebecca A; Campbell, Peter T; Guinter, Mark A; Patel, Alpa V (Cancer epidemiology, biomarkers & prevention, 2022)
Sugar-sweetened beverage (SSB) consumption may be associated with cancer mortality independent of, or indirectly through, established influences on increased body adiposity.BACKGROUNDSugar-sweetened beverage (SSB) consumption may be associated with cancer mortality independent of, or indirectly through, established influences on increased body adiposity.We examined the associations of SSBs and artificially-sweetened beverages (ASB) with mortality from all-cancers combined, obesity-related cancers combined, and 20 cancer types, among men and women in the Cancer Prevention Study-II (CPS-II) prospective cohort. In 1982, 934,777 cancer-free participants provided information on usual SSB and ASB consumption. Deaths were identified through 2016. Multivariable Cox proportional hazards regression models examined associations of beverage types with cancer mortality, without and with BMI adjustment.METHODSWe examined the associations of SSBs and artificially-sweetened beverages (ASB) with mortality from all-cancers combined, obesity-related cancers combined, and 20 cancer types, among men and women in the Cancer Prevention Study-II (CPS-II) prospective cohort. In 1982, 934,777 cancer-free participants provided information on usual SSB and ASB consumption. Deaths were identified through 2016. Multivariable Cox proportional hazards regression models examined associations of beverage types with cancer mortality, without and with BMI adjustment.During follow-up, 135,093 CPS-II participants died from cancer. Consumption of ≥2 SSB drinks/day vs. never was not associated with all-cancer mortality, but was associated with increased risk of obesity-related cancers [HR, 1.05; 95% confidence intervals (CI), 1.01-1.08; Ptrend = 0.057], which became null after adjustment for BMI. SSBs were associated with increased mortality from colorectal (HR, 1.09; 95% CI, 1.02-1.17; Ptrend = 0.011), and kidney (HR, 1.17; 95% CI, 1.03-1.34; Ptrend = 0.056) cancers, which remained after BMI adjustment. A positive association of ASB consumption with obesity-related cancers (HR, 1.05; 95% CI, 1.01-1.08; Ptrend = 0.001) was null after controlling for BMI; however, an increased risk of pancreatic cancer was robust to BMI adjustment (HR, 1.11; 95% CI, 1.02-1.20; Ptrend < 0.008).RESULTSDuring follow-up, 135,093 CPS-II participants died from cancer. Consumption of ≥2 SSB drinks/day vs. never was not associated with all-cancer mortality, but was associated with increased risk of obesity-related cancers [HR, 1.05; 95% confidence intervals (CI), 1.01-1.08; Ptrend = 0.057], which became null after adjustment for BMI. SSBs were associated with increased mortality from colorectal (HR, 1.09; 95% CI, 1.02-1.17; Ptrend = 0.011), and kidney (HR, 1.17; 95% CI, 1.03-1.34; Ptrend = 0.056) cancers, which remained after BMI adjustment. A positive association of ASB consumption with obesity-related cancers (HR, 1.05; 95% CI, 1.01-1.08; Ptrend = 0.001) was null after controlling for BMI; however, an increased risk of pancreatic cancer was robust to BMI adjustment (HR, 1.11; 95% CI, 1.02-1.20; Ptrend < 0.008).SSB consumption was associated with higher mortality from certain cancers, partially mediated through obesity. Associations of ASB consumption and increased pancreatic cancer risk merit further study.CONCLUSIONSSSB consumption was associated with higher mortality from certain cancers, partially mediated through obesity. Associations of ASB consumption and increased pancreatic cancer risk merit further study.Future research should consider the role of BMI in studies of sweetened beverages and cancer risk. These results should inform policy regarding sweetened beverage consumption.IMPACTFuture research should consider the role of BMI in studies of sweetened beverages and cancer risk. These results should inform policy regarding sweetened beverage consumption.